Determinants of the Incidence of Acute Respiratory Infections (ARIs) in Children Under Five at the Getengan Community Health Center, Tana Toraja Regency - Zadrak Tombeg; Erni Yetti R; Anto J Hadi; Ahmad Safii Hasibuan; Suherman Rate; Fitri Rahma Handayani; Nayodi Permayasa (Journal of Public Health and Pharmacy)
Introduction: Acute Respiratory Infections (ARIs) remain one of the main health problems among toddlers in Indonesia, including in Tana Toraja Regency. The objective of the study was to identify the determinants of the incidence of Acute Respiratory Infections (ARIs) on Toddlers at Getengan Health Center Tana Toraja Regency.